LEGAL AND INSTITUTIONAL ISSUES IN THE STATE POLICY FOR DEVELOPMENT AND SUPPORT OF SMALL AND MEDIUM BUSINESSES - E. M. Bukhvald (Финансы: теория и практика)
This article discusses ways to improve the legal and institutional framework for public policy aimed at developing and supporting small and medium businesses. It points to a need to increasingly direct basic forms and priorities of this support to the fulfillment of key tasks of innovative modernization of the Russian economy. The article draws attention to the importance of harmonizing existing legislation on the development of small and medium enterprises in the Russian Federation with other systemic laws in the area of economic regulation, namely the laws on strategic planning, industrial policy, public-private partnership, and innovation. It stresses the need to reflect in the system of institutions as well as in specific measures for developing small and medium businesses a growing maturity of this group of business entities which are focused on the real economic sector and interaction between large, small and medium enterprises. Under the current circumstances, small businesses cannot act neither as a significant damper for social and economic costs of crisis phenomena observed for the last two years nor as a sufficiently powerful factor in innovative modernization and restructuring of the Russian economy. State (federal) support for small and medium businesses has been “stratified” between the state and departmental programs implemented by various federal executive bodies. In this regard the measures directed to increase of the common institutional maturity of the Russian economy have to be a principal direction of a state policy concerning MSP. These are the changes aimed at creation of the common favorable enterprise and investment environment at the heart of which - fight against corruption and irrational administrative barriers; qualitative statistical information on development of the Russian MSP at all levels and, of course, the maximal binding of profitable sources of regional and local budgets to dynamics of development of medium-sized forms of economic activity in territories.